1980
DOI: 10.1002/art.1780230209
|View full text |Cite
|
Sign up to set email alerts
|

Collagen types synthesized in dermal fibroblast cultures from patients with early progressive systemic sclerosis

Abstract: Progressive systemic sclerosis (PSS) is a generalized disease characterized by inflammatory, fibrotic, and degenerative changes of connective tissue (1). The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
2

Year Published

1980
1980
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(24 citation statements)
references
References 16 publications
1
21
0
2
Order By: Relevance
“…Fibroblasts, either derived from cords of Dupuytren's disease (DF) or control tissues (CF), were isolated by using the explant culture technique as described [14] and grown in DMEM (Glucose 1.0 g/l, NaHCO 3 3.7 g/l, NAcetyl-L-alanyl-L-glutamine 1.0289 g/l, BIOCHROM) supplemented with 10% FCS, 40 µg/ml Gentamycin (GIBCO/BRL) without additional growth factors in 75 cm 2 culture flasks. All cultures were maintained at 37°C, 5% CO 2 in a humidified atmosphere.…”
Section: Cell Culturementioning
confidence: 99%
“…Fibroblasts, either derived from cords of Dupuytren's disease (DF) or control tissues (CF), were isolated by using the explant culture technique as described [14] and grown in DMEM (Glucose 1.0 g/l, NaHCO 3 3.7 g/l, NAcetyl-L-alanyl-L-glutamine 1.0289 g/l, BIOCHROM) supplemented with 10% FCS, 40 µg/ml Gentamycin (GIBCO/BRL) without additional growth factors in 75 cm 2 culture flasks. All cultures were maintained at 37°C, 5% CO 2 in a humidified atmosphere.…”
Section: Cell Culturementioning
confidence: 99%
“…More than a decade ago, it was observed that fibroblasts from involved skin of patients with scleroderma synthesized increased levels of collagen in vitro (1,2); today the mechanism remains unknown (3)(4)(5)(6). During this period, observations ofthe pathogenesis of scleroderma have focused on vascular and microvascular lesions; on evidence of endothelial damage; on platelet adhesion, aggregation, and release; and on the subsequent activation both of smooth muscle cells to produce the intimal proliferation and of interstitial fibroblasts to produce fibrosis (7)(8)(9)(10).…”
mentioning
confidence: 99%
“…Additional evidence supporting the concept that the collagen found in CHL cell layers is composed of B chains and information about the localization of this material in culture was obtained by staining CHL cell layers with affinity-purified antibody specific for the B chain and molecules containing B chains (20,21). The majority of the immunoreactive material synthesized by CHL cells was localized in an extracellular matrix surrounding the cells; only a small amount of intracellular staining was observed (Fig.…”
Section: Resultsmentioning
confidence: 64%
“…Immunohistochemical staining of air-dried CHL cell layers was performed by using a specific antibody prepared against the human B chain as described (20,21).…”
mentioning
confidence: 99%